PENGARUH KEMUDAHAN DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN LAYANAN STREAMING NETFLIX - Siti Badriah; Suryari Purnama (JURNAL LENTERA BISNIS, 2022)
Based on the reviews of potential customers, there are complaints in the form of difficulties in purchasing a Netflix subscription account. There are negative comments about the Netflix service through the Google Playstore service, indicating an electronic word of mouth problem. Customers who are willing to leave bad reviews and comments about Netflix, will create a bad perception of Netflix.This study aims to determine the Effect of Easy to use and E-WOM on Purchase Decisions on Netflix Movie Streaming Services.  The  population  is  Netflix  Movie  Streaming  Service  subscribers  with  a  sample  of   100 respondents. The sampling technique used was the purposive sampling technique, with the criteria for testing respondents aged 17 years, customers who had purchased a Netflix subscription account  within the last 3 months, followed the Netflix Instagram account. access Netflix at least once a week. The test tool used is Multiple Linear Regression. The results of this study indicate that each variable Ease and E - WOM has a positive and significant effect on purchasing decisions. Then Ease and E -WOM have a joint effect on Purchase Decisions on Netflix Movie Streaming Services. This means that the better the ease of a system, the better the conversation on social media turns out to improve purchasing decisions. This research is expected to be used as the basis for evaluating, determining strategies and policies that can be applied in the future by the Netflix company so that it remains the main choice in becoming a Movie Streaming Service.Keywords: Easy to Use, E-WOM, Purchase Decisions.